(untitled) (Faridpur Medical College Journal, 2013)
Pulmonary hypertension is a relatively common disorder that leads to right heart failure if untreated. Symptoms and signs of pulmonary hypertensionare often subtle and nonspecific. As a result a significant delay between the onset of symptoms and the diagnosis of pulmonary hypertension is common. Recently improved understanding of the pathophysiology of pulmonary hypertension leads to various treatment options that enable us to treat this disorder more efficiently. DOI: http://dx.doi.org/10.3329/fmcj.v7i2.13506 Faridpur Med. Coll. J. 2012;7(2):82-87